Sobre Marie-Noëlle Chamoux, Danièle Dehouve, Cécile Gouy-Gilbert y Marielle Pepin Lehalleur (coords.), Prestar y pedir prestado: relaciones sociales y crédito en México, del siglo XVI al XX - Zebadúa, Emilio (El Colegio de México, A.C., 1996)
-